2018
DOI: 10.1097/md.0000000000013346
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of risedronate in improving bone mineral density in patients undergoing total hip arthroplasty

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Meta-analyses of randomized controlled trials of oral bisphosphonates found that treatment preserves periprosthetic BMD for more than 5 years after THA. 13,14 In addition, 1 year of bisphosphonate treatment prevents early reduction of hip BMD after THA regardless of osteoporosis diagnosis. 15 In 20,784 primary TKA patients 65 years and older, patients who did not use bisphosphonates had a more than 3 times greater risk of revision than patients who used bisphosphonates and bisphosphonates had a protective effect even for patients with normal BMD postoperatively.…”
mentioning
confidence: 99%
“…Meta-analyses of randomized controlled trials of oral bisphosphonates found that treatment preserves periprosthetic BMD for more than 5 years after THA. 13,14 In addition, 1 year of bisphosphonate treatment prevents early reduction of hip BMD after THA regardless of osteoporosis diagnosis. 15 In 20,784 primary TKA patients 65 years and older, patients who did not use bisphosphonates had a more than 3 times greater risk of revision than patients who used bisphosphonates and bisphosphonates had a protective effect even for patients with normal BMD postoperatively.…”
mentioning
confidence: 99%
“…The follow-up ranged from 6 months to 4 years. After 3 months of medication there was increase of BMD only in Gruen zones 1,2,6,7 compared with the control group (p<0.05) while at 6 and 12 months was observed a significant beneficial effect of oral risedronate on preservation of BMD in all Gruen zones compared with the control group (p<0.05) 19 .…”
Section: A) Bisphosphonatesmentioning
confidence: 73%
“…Fourthly, we find that there are another four similar meta-analyses published online in 2018 [5][6][7][8]. All of them were performed following the guideline of PRISMA and four declared that they were the first meta-analysis on this topic, while none of them had a protocol registration in any platform, such as the Cochrane Library and PROSPERO.…”
Section: Dear Editorsmentioning
confidence: 88%